Moonflower murders [compact disc, unabridged] : a novel - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Susan Ryeland, 2020)
Retired publisher Susan Ryeland is living the good life. She is running a small hotel on a Greek island with her long-term boyfriend Andreas. It should be everything she's always wanted. But is it? And then the Trehearnes come to stay. The strange and mysterious story they tell, about an unfortunate murder that took place on the same day and in the same hotel in which their daughter was married, a picturesque inn on the Suffolk coast named Farlingaye Halle, fascinates Susan and piques her editor's instincts. When the Trehearnes reveal that their daughter Cecily is now missing, Susan knows that she must return to England and find out what really happened.